Finding Santana - Jolliffe, Jill, 1945- (Wakefield Press, 2011)
Tells of Joliffe's clandestine 1994 journey across the Indonesian archipelago pursued by the Suharto dictatorship's notorious secret police to interview East Timorese guerrilla commander Nino Konis Santana. Part memoir, part adventure story, it is written from the diaries of the journey and interwoven with those of intrepid nineteenth-century traveller Anna Forbes, who also narrowly escaped death in the East Timor mountains.